Thermal behavior of alkali-activated fly ash/slag with the addition of an aerogel as an aggregate replacement. (February 2020) - Seo, Joonho; Bae, S.J.; Jang, D.I.; Park, Solmoi; Yang, Beomjoo; Lee, H.K.
Abstract: The present study investigated the thermal behavior of alkali-activated fly ash/slag with the addition of an aerogel as an aggregate replacement. Samples having aggregate-to-aerogel replacement ratios of 25, 50, and 75% by volume were fabricated and were exposed to temperatures of 200 °C, 400 °C, 600 °C or 800 °C. Water contact angle and thermal conductivity tests were carried out to assess the dispersion of the aerogel in an alkaline environment. X-ray diffractometry, mercury intrusion porosimetry, compressive strength test and thermogravimetry were conducted to investigate the thermal evolution of the reaction products, the pore structures and the mechanical strength. The results revealed that the incorporated aerogel mitigated thermal expansion up to 600 °C while also inducing rapid thermal shrinkage above 600 °C. Meanwhile, the pore structures of the samples with high aerogel contents were scarcely altered upon exposure to high temperatures, showing a level similar to those observed at 25 °C.